The Development of Geographic Information System for Wi-Fi Coverage at Block A1, UTHM Pagoh - Vijaya Shankar, Sarinisaa; Abdul Sukor Sarif (Progress in Engineering Application and Technology, 2022)
Geographical Information System (GIS) is a computer-based information system which digitally records and analyzes geographic elements on the earth’s surface based on Tobler’s first law of geography. This study’s objective is to analyze the existing Wi-Fi location at the campus area. Followed by, to study problems of Wi-Fi coverage at campus and to determine the location with highest Wi-Fi coverage at the campus area. At the conclusion of this research, it is predicted that a suitable location with optimum network coverage in the campus would be identified.